The Relationship between Pricing and Brand Strategy with Customer Satisfaction Levels - Pandi Putra; Basri Modding; Bakhtiar Tijjang; Nurfadhilah Nurfadhilah; Safrida Safrida (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The telecommunications industry in Indonesia faces intense competition, prompting companies like Telkomsel to optimize pricing and brand strategies to enhance customer satisfaction. This study examines the influence of price and brand equity on customer satisfaction among Telkomsel’s 5G service users at the PT. Telkomsel Branch in Pinrang Regency. Employing a quantitative descriptive approach, data were collected from 45 respondents through incidental sampling using observation, interviews, questionnaires, documentation, and literature reviews. Multiple linear regression analysis was conducted using SPSS 26. The findings reveal that price significantly affects customer satisfaction (t = 2.649, p = 0.011 < 0.05), indicating that competitive pricing enhances perceived value. Brand equity also has a significant impact (t = 7.665, p = 0.000 < 0.05), with its stronger influence (beta = 0.707) highlighting the role of brand reputation in driving satisfaction. Together, price and brand equity explain 72.5% of satisfaction variance (F = 55.358, p = 0.000 < 0.05). The study concludes that Telkomsel should maintain competitive pricing and strengthen brand equity through enhanced network reliability and marketing to sustain customer loyalty in Pinrang Regency’s competitive market. These insights provide strategic recommendations for optimizing 5G service offerings.